Poverty and Corruption in Sri Lanka: An ARDL Bound Testing Technique and Error Correction Model - Godwin Phillip, P.; Neruja, N. (Eastern University, Sri Lanka, 2021)
The objective of this research paper is to empirically investigate the impact of corruption on poverty in Sri Lanka over the period 1996-2016 using the secondary data. ADF unit root test was applied to check the variables stationary and an ARDL bound testing approach is used to investigate co-integration among the study variables such as poverty, corruption, economic growth, FDI, inflation and population. The results of ARDL test confirmed that there is a long run relationship among poverty, corruption, and other explanatory variables of poverty over the study period. The long-run estimates indicate that Corruption, GDP, foreign direct investment, and inflation rate have impact on poverty. It revealed that a 1 percent increase in corruption would increase the poverty rate by 0.726 percent in the long run and 1 percent rise in corruption would increase the poverty rate by 0.601 percent in the short run. As a result, the government should pursue policies that will substantially reduce corruption, thereby the government policy implication should focus on reduce the corruption to improve the standards of living to eliminate poverty in Sri Lanka.
Keywords: Corruption perception Index; Poverty; GDP; Inflation; ARDL; Error Correction Model